Exercise to Enhance Smoking Cessation: the Getting Physical on Cigarette Randomized Control Trial. Issue 3 (20th January 2016) - Prapavessis, Harry; De Jesus, Stefanie; Fitzgeorge, Lindsay; Faulkner, Guy; Maddison, Ralph; Batten, Sandra
Abstract: Background: Exercise has been proposed as a useful smoking cessation aid. Purpose: The purpose of the present study is to determine the effect of an exercise-aided smoking cessation intervention program, with built-in maintenance components, on post-intervention 14-, 26- and 56-week cessation rates. Method: Female cigarette smokers ( n  = 413) participating in a supervised exercise and nicotine replacement therapy (NRT) smoking cessation program were randomized to one of four conditions: exercise + smoking cessation maintenance, exercise maintenance + contact control, smoking cessation maintenance + contact control or contact control. The primary outcome was continuous smoking abstinence. Results: Abstinence differences were found between the exercise and equal contact non-exercise maintenance groups at weeks 14 (57 vs 43 %), 26 (27 vs 21 %) and 56 (26 vs 23.5 %), respectively. Only the week 14 difference approached significance, p  = 0.08. Conclusions: An exercise-aided NRT smoking cessation program with built-in maintenance components enhances post-intervention cessation rates at week 14 but not at weeks 26 and 56.